Synopsis of Zikanita Lane (Coleoptera: Cerambycidae: Lamiinae) - Machado, Vanessa S.; Monné, Marcela L. (Zootaxa, 2011)
Lane (1943) proposed the genus Zikanita for Zikanita perpulchra Lane, 1943 from Rio de Janeiro, considering it close to Cosmotomidius Melzer, 1931. Marinoni & Martins (1978) considered Acanthoderes (Trichacanthoderes) Tippmann, 1960 a synonym of Zikanita, and transferred the two species, Z. biocellata (Tippmann, 1960) and Z. argenteofasciata (Tippman, 1960), both described from Peru.